Antibacterial Compounds from Marine Vibrionaceae Isolated on a Global Expedition - Lone Gram; Charlotte H. Gotfredsen; Thomas O. Larsen; Matthias Wietz; Maria Mansson (Marine Drugs, 2010)
On a global research expedition, over 500 bacterial strains inhibitory towards pathogenic bacteria were isolated. Three hundred of the antibacterial strains were assigned to the Vibrionaceae family. The purpose of the present study was to investigate the phylogeny and bioactivity of five Vibrionaceae strains with pronounced antibacterial activity. These were identified as Vibrio coralliilyticus (two strains), V. neptunius (two strains), and Photobacterium halotolerans (one strain) on the basis of housekeeping gene sequences. The two related V. coralliilyticus and V. neptunius strains were isolated from distant oceanic regions. Chemotyping by LC-UV/MS underlined genetic relationships by showing highly similar metabolite profiles for each of the two V. coralliilyticus and V. neptunius strains, respectively, but a unique profile for P. halotolerans. Bioassay-guided fractionation identified two known antibiotics as being responsible for the antibacterial activity; andrimid (from V. coralliilyticus) and holomycin (from P. halotolerans). Despite the isolation of already known antibiotics, our findings show that marine Vibrionaceae are a resource of antibacterial compounds and may have potential for future natural product discovery.